Stable P and distal dynamical systems - S. S. Prasad; Anant Kumar (International Journal of Mathematics and Mathematical Sciences)
In this paper we study the behavior of dynamical systems in uniform space which are Poisson stable and distal. The main results are that the trajectories of such motions are closed and every almost periodic motion is stable P and distal. In complete uniform space, this motion is periodic, Lagrange stable and recurrent.